Human rights, comprehensive sex education and practices: mainstreaming curricular axes for Teacher Training at UNLPam (Praxis Educativa, 2016)
This article deals with Teacher Training at UNLPam through three different instances of transversality in the teaching process in the last five years. Those institutional decisions to integrate contents materialized in a programs change that created the Practices Field; the creation of a program to introduce human rights in the curriculum and the establishment of an extra-curricular chair to start a similar process in comprehensive sex education matters. Although the three aims point to a comprehensive training, with critical and social commitment, the results have been -up to now- very different in each case. This text thinks over the dissimilar processes developed, the analogies, differences and intervening actors, in the light of the significant contributions of decolonizing pedagogies, Latin American feminism and the communitarian paradigm of human rights. The current political context is analyzed to propose some keys to go on working in order to build a new epistemology of Teacher Training in a collaborative way and from its own place of enunciation.
Keywords: holistic training; human rights; sex education; pre-professional practices; located epistemology